Case Report: Intravascular ultrasound-guided management of acute myocardial infarction in a rare coronary artery case with multiple ostia and varied lesions - He, Huabin; Ao, Qin; Chen, Jianhai; Zhang, Jun; Yuan, Xiangyang (Frontiers in Cardiovascular Medicine, 2024)
Anomalous origin of the coronary artery (AOCA) in coronary arteries represent a rare congenital variation, especially when three or more openings coexist, accompanied by conditions such as myocardial infarction, acute heart failure, and severe stenosis in three vessels, making it even rarer. This study reports a rare case of a patient admitted for the first time with acute myocardial infarction. Coronary angiography revealed four openings, along with the aforementioned rare conditions. Guided by intravascular ultrasound (IVUS), treatments were administered for different lesions in various vessels. IVUS confirmed a rare case with a 1 mm extremely short left main coronary artery and three openings. The two-year follow-up results for this patient are deemed satisfactory, indicating a favorable prognosis.